Pengaruh profitabilitas dan ukuran perusahaan terhadap nilai perusahaan dengan csr sebagai variabel moderasi - Ramadhani, Fitria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aimed to explain the effect of profitability and firm size on firm value with Corporate Social Responsibility (CSR) as a moderating variable. The population of this research is the form of manufacturing companies in the consumer goods and consumption which are listed on Indonesian Stock Exchange (IDX) during 2018-2020. Determination of the sample using purposive sampling technique and obtained as many 30 manufacturing companies with a total of 90 observation. The data analysis technique used Moderated Regression Analysis (MRA). The result of this study indicate that profitability has a positive and significant effect on firm value, firm size has negative and insignificant effect on firm value, CSR is not able to moderate the effect of profitability and firm size on firm value.